Soil-Borne Vegetable Diseases in Shivalaya, Jajarkot: Farmer Perceptions, Management Practices and Constraints - Thapa, Sundar Bishwakarma; Rokaya, Ramesh Bahadur; Ghimire, Ashish (Journal of the Institute of Agriculture and Animal Science, 2025)
Soil-borne diseases are a serious threat to vegetable crops. This study aimed to investigate farmers' perception regarding soil-borne diseases of vegetables and their management practices in Shivalaya Rural Municipality, Jajarkot. A semi-structured interview was conducted with 60 vegetable-growing farmers to collect data. The study found that 91.7% of respondent farmers encountered plant diseases in their fields; however, only 73.3% were acquainted with soil-borne diseases. Respondents indicated damping-off as the most important soil-borne disease (index value: 0.90) based on a ranking study, followed by wilt (0.78) and root and collar rot (0.59). Among the respondents, 63.3% practiced non-chemical methods, and of these, 97.9% applied bio-pesticides prepared by themselves, while the rest used commercially manufactured Trichoderma. A total of 71.7% of farmers had received support from governmental and non-governmental organizations; however, most were highly unsatisfied with the support received. The majority of farmers (78.3%) indicated the influence of climate change on soil-borne diseases, based on their perception of increased frequency and severity in recent years. Besides, the majority of the respondents also perceived that the incidence of soil-borne diseases was affected by season as well as the type of crops. Barriers to effective disease management included a lack of knowledge, costlier inputs, and limited resource availability. The study highlights the importance of accessible extension services, awareness programs, and policy support for capacity building to manage soil-borne diseases. By considering farmers' perceptions, this study provides valuable information for developing effective disease management strategies, enhancing agricultural sustainability and productivity.